Health assessment of Gwoza residents in Borno State, Nigeria: A Case Study - Ogbonna John D.N., Bello mustapha, Eke Ifeanyi G., Kenechukwu Franklin C, Agubata Chukwuma (Journal of Applied Pharmaceutical Science)
The awareness of blood pressure (BP), weight, height, genotype, sickle cell disease (SCD) and blood group in most rural communities of Nigeria is low. The community survey and assessment was carried out on 150 healthy adult (age 18 and above) individuals, out of which 138 were male and 12 were female at Gwoza, Borno State, Nigeria in September 2010. Eligibility is dependent on six-minute-walk distance, ensuring that patients are moderately but not too severely functionally impaired, thereby maximizing the likelihood of detecting a favorable response to questionnaire and BP measurement. The assessment showed that 62.67 % and 2.66 % of the sample population had normal and stage 2 hypertensions respectively. The age distribution showed that 64 % were between 18-29 years old and nobody was above 60 years. The percentage of underweight, normal weight, over weight and obese people were 9.33 %, 72 %, 16 % and 2.67 % respectively. A 37.34 % and 58.67 % of the people were of blood group A with Rh+ and blood group O with Rh+ respectively while 13.33 % of the respondents had SCD. The study was able to establish the extent of awareness and prevalence of BP, body mass index (BMI), genotype, SCD and blood group in the community.
Keywords: Body mass index,blood pressure,blood group,assessment,genotype.